Diagnostic Exome Sequencing Identifies Two Novel IQSEC2 Mutations Associated with X‐Linked Intellectual Disability with Seizures: Implications for Genetic Counseling and Clinical Diagnosis. Issue 3 (4th December 2013) - Gandomi, Stephanie K.; Farwell Gonzalez, K. D.; Parra, M.; Shahmirzadi, L.; Mancuso, J.; Pichurin, P.; Temme, R.; Dugan, S.; Zeng, W.; Tang, Sha
Abstract: Intellectual disability is a heterogeneous disorder with a wide phenotypic spectrum. Over 1, 700 OMIM genes have been associated with this condition, many of which reside on the X‐chromosome. The IQSEC2 gene is located on chromosome Xp11.22 and is known to play a significant role in the maintenance and homeostasis of the brain. Mutations in IQSEC2 have been historically associated with nonsyndromic X‐linked intellectual disability. Case reports of affected probands show phenotypic overlap with conditions associated with pathogenic MECP2, FOXG1, CDKL5, and MEF2C gene mutations. Affected individuals, however, have also been identified as presenting with additional clinical features including seizures, autistic‐behavior, psychiatric problems, and delayed language skills. To our knowledge, only 5 deleterious mutations and 2 intragenic duplications have been previously reported in IQSEC2 . Here we report two novel IQSEC2 de novo truncating mutations identified through diagnostic exome sequencing in two severely affected unrelated male probands manifesting developmental delay, seizures, hypotonia, plagiocephaly, and abnormal MRI findings. Overall, diagnostic exome sequencing established a molecular diagnosis for two patients in whom traditional testing methods were uninformative while expanding on the mutational and phenotypic spectrum. In addition, our data suggests that IQSEC2 may be more common than previously appreciated, accounting for approximately 9 % (2/22) of positive findings among patients with seizures referred for diagnostic exome sequencing. Further, these data supports recently published data suggesting that IQSEC2 plays a more significant role in the development of X‐linked intellectual disability with seizures than previously anticipated.